Achilles enthesitis defined by ultrasound is not associated with clinical enthesitis in patients with psoriatic arthritis. Issue 2 (16th August 2017) - Michelsen, Brigitte; Diamantopoulos, Andreas P; Soldal, Dag Magnar; Hammer, Hilde Berner; Kavanaugh, Arthur; Haugeberg, Glenn
Abstract : Objective: To compare clinical and ultrasonographic (US) evaluation of Achilles enthesitis in patients with psoriatic arthritis (PsA). Methods: The Achilles insertion of outpatients with PsA was examined by clinical assessment of tenderness and US evaluation of (1) inflammatory activity (defined as the presence of power Doppler signal, tendon thickening and/or hypoechogenicity) and (2) structural damage (defined as the presence of erosions, calcifications and/or enthesophytes). Univariate and multivariate logistic regression analyses were performed0.4 to explore the associations between clinical characteristics and US scores. Results: 282 Achilles tendons in 141 patients with PsA were assessed. Mean (SD) age was 52.4 (10.2) years, disease duration 9.5 (6.6) years and 50.4% were females. Palpatory tenderness was found in 88 (31.2%), US-verified inflammatory activity in 46 (16.3%) and structural damage in 148 (52.5%) of the Achilles. Total US scores, as well as their components, were similar for patients with and without palpatory tenderness. None of the clinical characteristics were associated with inflammatory activity. Age, body mass index (BMI), regular physical exercise and current use of biological disease-modifying antirheumatic drugs (bDMARDs) were associated with structural damage. Conclusion: There appears to be a lack of association between clinical and US signs of Achilles enthesitis in PsA. Age, BMI, regular physical exercise and current use of bDMARDs were associated with structural damage on US.